Pengaruh Beberapa Konsentrasi Kolkisin Terhadap Hasil dan Perubahan Karakteristik Stomata Tanaman Jagung Manis (Zea mays L. saccharata) Varietas Paragon - Nahwah, Firzanah; Rosyidah, Anis; Muslikah, Siti (Folium : Jurnal Ilmu Pertanian, 2024)
Corn is one of the important food crops in Indonesia and has a strategic role in the national economy, given its multipurpose function, as a source of food, feed, and industrial raw materials. The need for corn is increasing along with the increasing population growth and the development of the feed and food industry. Efforts to improve the quality and quantity of corn productivity can be done by carrying out genetic improvements. Mutation induction using colchicine is expected to improve plant properties, both qualitatively and quantitatively, especially in increasing plant productivity.Colchicine is capable of inducing plants to become polyploid plants at the right concentration and time. Plants treated with colchicine showed changes in characters such as seed color, plant height, number of leaves, leaf width, stomata width, and flowering time. This study aims to determine the effect of various concentrations of colchicine on yield and changes in stomata characteristics of sweet corn (Zea mays L. saccharata) Paragon variety. Yield and quality of corn plants D4 treatment (600 ppm) is the best treatment for yield parameters and quality of corn plants, on the characteristics of the stomata of corn plant leaves the D4 treatment (600 ppm) is a good treatment for the parameters of length, width, and area of ​​stomata sweet corn plant leave.